KEKERASAN, KORUPSI DAN PEMILUKADA - Fitriyah, Fitriyah (Faculty of Social and Political Sciences Diponegoro University, 2011)
Abstract :Corruption scandals surrounding of local budgeting is one of structural violence, is paradox to increase the efficiency and responsiveness of the public sector. Local head elections increase in the number of regional heads who are involved in corrupt acts. There are 17 governors and 138 regents and mayors across the country are currently under investigation or serving prison sentences related to corruption. Why does corruption happen? The factor behind the rampant political corruption is regulation of voting system led to expensive political cost, not only in campaign funding but also in candidate recruitment system. In order to minimize the potential for corruption and avoid the temptation of using of regional budgets by recover election laws, we must democratize party recruitment and we must limit campaign spending by regional head candidatesKey words: violence, corruption, local electionspermalink:http://ejournal.undip.ac.id/index.php/forum/article/view/3152